PENERAPAN TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BILANGAN PECAHAN SISWA KELAS V SD - Rahmatikasari, Ulfi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Ulfi Rahmatikasari1, Imam Suyanto2, Warsiti3 e-mail: rahmaulfi@yahoo.com 1 Mahasiswa PGSD FKIP UNS 2, 3 Dosen PGSD FKIP UNS Abstract: The Application of Team Assisted Individualization (TAI) Type in Increasing Mathematic About Fraction Number Learning 5th Grade Student State Elementary School. The purpose of this research was increasing fraction number learning in 5th grade of state elementary school. This research was colaborative classroom action research. This research conducted in 2 cycle consist of planning, action, observation, and reflection. Data source was taken from observer, 5th grade students and 5th grade teacher. Data collecting techniques were observation, test, questionaire, and documentation. The validity of data source used a triangulation methods and data source. The learning has been increased from cycle I to cycle II. The percentage of the teacher teach by applied TAI type in cycle I was 68,72% and cycle II was 85,85%. The students learning process cycle I was 66,60% and cycle II was 85,25%. The students mastery learning percentage reached 88,46% in cycle I and 87,18% in cycle II. There were obstacles on the application of TAI type and it has been found appropriate solutions. The conclusion of this research that the application of TAI type can increase fraction number learning 5th grade elementary school. Keywords: Team Assisted Individualization (TAI) type, fraction number ,learning. Abstrak: Penerapan Tipe Team Assisted Individualization (TAI) dalam Peningkatan Pembelajaran Matematika Tentang Bilangan Pecahan Kelas V SD. Penelitian ini bertujuan meningkatkan pembelajaran bilangan pecahan siswa kelas V SD. Penelitian ini berupa penelitian tindakan kelas kolaboratif. Penelitian dilaksanakan dalam 2 siklus yang terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Teknik pengumpulan data dengan observasi, tes, kuesioner, dan dokumentasi. Validitas data menggunakan teknik triangulasi data dan sumber data. Pembelajaran mengalami peningkatan dari siklus I hingga siklus II. Persentase guru mengajar dengan menerapkan tipe TAI pada siklus I 68,72% dan siklus II 85,85%. Proses belajar siswa pada siklus I 66,60% dan siklus II 85,25%. Ketuntasan belajar siswa mencapai 88,46% pada siklus I dan 87,18% pada siklus II. Dalam penerapan tipe TAI terdapat kendala dan telah ditemukan solusi yang tepat. Simpulan penelitian ini adalah penerapan tipe TAI dapat meningkatkan pembelajaran bilangan pecahan siswa kelas V SD. Kata kunci: tipe Team Assisted Individualization (TAI), pembelajaran, bilangan pecahan.